Simulation study of an artificial fish swarm algorithm and application to UAV path planning - Wang, Xuyang (Nanyang Technological University, 2024)
In recent years, with the rapid change of science and technology, complex optimization problems are more and more common in many fields. These problems are very tricky in high-dimensional, nonlinear and multi-constraint scenarios, and traditional optimization methods are often difficult to deal with them efficiently and achieve the expected optimization results. How to solve complex optimization problems efficiently, quickly and accurately and apply them to the real world has become a big challenge. Faced with this challenge, Artificial Fish Swarm Algorithm (AFSA) shows its unique advantages in solving complex optimization problems with its unique swarm intelligence search mechanism.